2020
DOI: 10.1590/0074-02760200055
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of first and second-line drug resistance-associated mutations among resistant Mycobacterium tuberculosis clinical isolates from São Paulo, Brazil

Abstract: BACKGROUND Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, and the number of new cases of multidrug resistant TB (MDR-TB), pre extensively drug-resistant TB (pre-XDR-TB) and extensively drugresistant TB (XDR-TB) has increased considerably worldwide.OBJECTIVES Herein, using 156 M. tuberculosis isolates from 106 patients previously classified as MDR or pre-XDR or XDR isolates, we investigated the genetic mutation profiles associated with phenotypic resistances in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
4
4
1
Order By: Relevance
“…In our study, we analysed the rrs gene and identified several substitutions associated with streptomycin (positions 514, 517, 888, and 906) or linked to cross-resistance to kanamycin, capreomycin, or amikacin (1401A>G). It is worth noting that this mutation has been found to confer high levels of resistance in previous studies [8,72,[88][89][90][91][92]. Moreover, our study identified two isolates with the -12C>T mutation in the eis promoter that have been associated with low-level kanamycin resistance, supporting previous research findings [93,94].…”
Section: Plos Onesupporting
confidence: 89%
“…In our study, we analysed the rrs gene and identified several substitutions associated with streptomycin (positions 514, 517, 888, and 906) or linked to cross-resistance to kanamycin, capreomycin, or amikacin (1401A>G). It is worth noting that this mutation has been found to confer high levels of resistance in previous studies [8,72,[88][89][90][91][92]. Moreover, our study identified two isolates with the -12C>T mutation in the eis promoter that have been associated with low-level kanamycin resistance, supporting previous research findings [93,94].…”
Section: Plos Onesupporting
confidence: 89%
“…A high proportion of STR resistance was observed in this study, which 60.7% of mutations was in the rpsL gene, agreeing that the k43R mutation is the most recurrent streptomycin resistance-associated mutation (32,79,81). In the rrs gene, the substitutions identified at positions 492, 514, 517, 888 and 906 previously have been associated with streptomycin resistance in TB (8,62,82,83); even though the 1401A>G, 1402C>T, and 1484G>T have been associated with cross-resistance to kanamycin, capreomycin or amikacin (84)(85)(86), only 1401A>G mutation was presented in 7.1% of isolates.…”
Section: Discussionsupporting
confidence: 77%
“…Several recent studies have examined the contribution of katG and inhA promoter mutations in drug-resistant TB isolates, and the results revealed significant geographic diversity across regions [ 25 27 ]. This study found that the most common mutation of MDR-TB was 34.7% (Ser531 → Leu + Ser315 → Thr), however, a study in Brazil showed that was 41.7% [ 28 ]. In our study, the mutation rate in katG 315 was 71.9%, which was higher than the mutation rates reported in Poland (66.0%) and Hebei Province, China (69.9%) [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%